O bem-estar no trabalho e suas relações com suporte e comprometimento organizacional afetivo: estudo de campo na Universidade Federal do Pampa (Unipampa) - Pires, Jaqueline Mota (2019)
This study aims to know the level of well-being in the work of the technical-administrative servers of the Federal University of Pampa (UNIPAMPA) and its relation with the constructs Perception of Organizational Support and Affective Organizational Commitment. The justification for focusing on these topics is based on the studies of several authors, such as: Locke (1976), when affirming that the individual's work well-being influences his professional behavior; Tamayo and Tróccoli (2002), highlighting the direct interference of the Organizational Support Perception on the worker's well-being; as well as Siqueira and Gomide Jr. (2008), when they point out the influence of this same variable on the Organizational Commitment of individuals; and finally, Lizote, Verdinelli and Nascimento (2017), when they affirm that, in order to succeed in the implementation of policies, strategies, objectives and institutional goals, workers need to present a high standard of Organizational Commitment. In this way, one can perceive the strategic relevance of these themes for contemporary organizations. In order to respond to the objectives of this research, a descriptive field study was developed with quantitative and qualitative approach that used three theoretical models: that of Paschoal and Tamayo (2008), to measure Well-being at work; the one of Siqueira (1995), to gauge the perception of Organizational Support; and a subscale of the Meyer and Allen model (1991), validated in Brazil by Medeiros and Enders (1998), to measure Affective Organizational Commitment. The sample collected for this study was 448 questionnaires answered, corresponding to 49.78% of the target population. There was an unsatisfactory perception regarding the Organizational Support construct and moderate levels of perception regarding Well-being and Affective Organizational Commitment by UNIPAMPA's technical-administrative staff. One hypothesis of the research was confirmed and two were partially confirmed, and the variables act as follows: 48.8% of all Affective Organizational Commitment was positively influenced by the variables Worker Well-Being and Perceived Organizational Support; and Well-being at work was positively impacted by the perceived Organizational Support variable, through its Affective (35.5%) and Cognitive (18.3%) dimensions. Given the confirmation that perceived Organizational Support is a significant predictor of Well-being in Work and Affective Organizational Commitment, incremental measures were proposed aiming to raise the perception of Organizational Support and, consequently, of its dependent variables, based on the literature review for this research.